Analisis Kadar Kafein Pada Fermentasi Kopi Arabika Desa Pandansari Kecamatan Paguyangan Kabupaten Brebes - Dyah Ayu Widowarti; Mei Natiqoh (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Coffee is one of the plantation commodities that is very important in world trade. The caffeine content in coffee is used as a brain stimulant and is useful for increasing concentration. Post-harvest coffee fermentation aims to break down compounds by microbes. This research aims to analyze caffeine levels in fermented Arabica coffee in Pandansari village and the effect of fermentation on coffee. The method used is the Parry reagent qualitative method and the quantitative method uses a UV-Vis Spectrophotometer. The positive qualitative test results for the presence of caffeine in samples with caffeine levels in pandansari fermented coffee with a fermentation time difference of 1 and 2 months were 13.4 mg caffeine or 1.347% and 4.2 mg 0.42% respectively. Fermentation affects the caffeine content of coffee as well as the resulting taste. Other influences that cause a decrease in caffeine content occur due to differences in varieties, post-harvest processes, roasting temperatures and steeping methods.